Evolution of The Revealed Comparative Advantage of Türkiye’s Agriculture and Textile Industries - Hakgeçirmez, Jale Ece; Šváb, Patrik; Horáková, Ludmila; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This study provides a longitudinal assessment of Türkiye’s trade specialisation in agriculture and textiles for the period 2014 – 2023. Employing the Revealed Comparative Advantage (RCA) and its symmetric transformation (RSCA), the study explores the direction of sectoral competitiveness, and position of Türkiye in this competition. Utilizing export data from the World Trade Organization and the Observatory of Economic Complexity, this study compares Türkiye with both global leaders and structurally similar countries. The findings do confirm a comparative advantage in textiles: average RCA values exceed 4.0 while RSCA stabilises around 0.61. On the other hand, agriculture sector displays a moderate yet ascending trajectory, with RCA averaging 1.67 and RSCA rising from 0.22 to 0.26 over the decade. Türkiye’s agricultural performance lagged behind Brazil and Canada though it remained comparable to North American exporters plus exceeded various European rivals. This improvement is linked to increased global demand, logistical reliability, and targeted public support in the aftermath of COVID-19. Cross-sectoral analysis highlights Türkiye’s core specialization as the textile industry, with emerging competitiveness represented by agriculture. Policy implications include the need to support high-value-added production in textiles and structural modernization in agriculture. The study gives a dual-sector longitudinal assessment using harmonized trade indices as well as multidimensional benchmarking strategies, it does contribute to the existing literature. It provides actionable insights for policymakers who seeks to enhance Türkiye’s trade competitiveness in a complex global environment.
Vedoucí práce: Patrik Šváb
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses